Annual Plan 2004-2005 (Volume-IV) National Capital Territory of Delhi - Planning Commission (Planning Commission, 2004)
Schemes providing water supply and sewerage facilities, Anti flood works and storm water drainage, desilting of nallahs and sewers in Delhi are included under this sector. The Delhi Jal Board of Govt, of Delhi is entrusted with the responsibility of production and distribution of water and treatment and disposal of sewage in Delhi. It provides water in bulk to NDMC and Cantonment Board for redistribution in their respective areas. Similarly the sewage is received in bulk from these two authorities for final, conveyance and disposal by Delhi Jal Board. In the areas under the jurisdiction of MOD, Delhi Jal Board is responsible for distribution of water and collection and disposal of sewage.
Planning Department, Government of National Capital Territory of Delhi